KEGIATAN MENGUBAH ANALISIS KARYA SASTRA MENJADI VIDEO KAMPANYE UNTUK MENUMBUHKAN KESADARAN MAHASISWA TERHADAP ISU PERUBAHAN IKLIM - Rane, Zakridatul Agusmaniar; Sofian, Nur Israfiyan; Safitri, Nuzul Hijrah; Arman, Arman (Universitas Halu Oleo, 2024)
Climate change is a factual issue that threatens the sustainability of human life on earth. it requires requires awareness from all levels of society to solve it. Students as intellectuals and agents of change should have full awareness of the urgency of this problem. But in reality, the students of English Literature study program UHO are still ignorant about this issue. Many of them are not familiar with this problem even though the issue of climate change has also been widely discussed in literary works and it has become its own genre, namely the green literature. Therefore, this worksop is intended to bring students closer to the phenomenon of climate change and make them aware that this is crucial to be tackled immediately. The method used is a training method in which students are guided to create climate change campaign videos based on the results of an analysis of the literary works they have done. The video is then disseminated through the YouTube channel and social media so that it can be accessed by the public. Assessment result of students literary analysis, students participation in discussion and campaign video they produced show that there has been an increase in students' understanding of climate change issues and their awareness of the risks of climate change issues. The results of this study are important because the impact of this program not only for the students but also spread out to other people who watch the campaign video.